DINAMIKA KETENAGAKERJAAN PADA WILAYAH PEDESAAN LAHAN KERING DI INDONESIA - Winarso, Bambang (Politeknik Negeri Lampung., 2014)
Indonesian Population increasing, the other side of the jobs that are limited, it is problems. As a country, agraris reality shows that availability of jobs was largely in agriculture sector. Inhabitant of indonesia development increasing while on the other side of the jobs that are limited, it is still problems. Its reality shows that availability of jobs was largely in agriculture sector. This was demonstrated by the source of livelihood largely from agriculture. As we know that in a domicile of agricultural labors being in the region with agroekosystem dryland which is sometimes tinged by the marginal land. Relating to employment been trying to highlight structure labour participation, especially in terms of level good chance and labour force, according to age, level of education, and types of work as well as people in rural areas, mobilization especially in village with agroekosistem dry land. The provinces that being the location where research is Lampung, South Sulawesi East Java, Central Java and West Java. The result showed that viewed from accessibility, job opportunities then accessibility of labor in this area use hasnt job opportunities outside agriculture. If the employment opportunities, the work got generally the same work often they do in the provenance as labor and transport services. Keywords: employment dynamics, rural areas and dryland